IMPLEMENTING LOCAL KNOWLEDGE TO EMPOWER FARMER WOMEN IN MANAGING SUSTAINABLE FOOD IN THE MANDIRI VILLAGE - Yanti, Rinda; Dharma, Setya; Elita, Nelson; Harmailis; Nilawati; Ibrahim, Hasan Ibrahim (International Journal of Research -GRANTHAALAYAH, 2023)
In order to create the socioeconomic conditions that will lead to self-sustaining and sustainable food security, it is crucial to analyze community empowerment models, particularly those that empower women, when evaluating the success of the food self-sufficient village program. In order to empower women in the management of sustainable, food-independent communities, research is being done to examine the state of food security, the role of institutions, and local knowledge. Survey techniques involving observation and interviews are included in the methodologies and data analysis. The findings demonstrated that the adequacy rate at the research site and the empowerment of farm women organizations in the area of family food security were not yet at their best. Some signs that empowerment has not been as effective as it could have been include: 1) respondents’ education is typically dominated by elementary school level, which significantly affects food patterns and their presentations; 2) land productivity is limited (0.5 ha) and dependent on rainwater; and 3) the majority of family expenditure is food expenditure and provides less than enough calories (2100 calories). The Nagari Institutional’s inadequate assistance and its local wisdom have a secondary impact on this problem. The women farmers’ group’s household food security status demonstrates that the empowerment of women farmers is not yet at its best, making independent food management unsustainable.